PELAKSANAAN PEMILIHAN PRESIDEN YANG SESUAI DENGAN PRINSIP KEDAULATAN RAKYAT DALAM SISTEM DEMOKRASI DI INDONESIA - Eko Wibowo; Ismail; Hartana (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
This research was submitted to answer two fundamental questions regarding the implementation of people’s sovereignty in the direct election of the President and Vice President in Indonesia, namely, what is the ideal ideal of the implementation of the presidential election in accordance with the principle of people’s sovereignty in the democratic system in Indonesia. This research is normative. This research is a library research conducted by examining library materials in the form of books, journals, research reports and/or secondary data that discuss the implementation of general elections in Indonesia in relation to people’s sovereignty. Application of laws and regulations (legal facts) that regulate the implementation of elections in Indonesia. From this research, the author concludes that in a democracy, people’s rights should be respected and upheld. There is no justification for government decisions that can harm people’s rights, let alone policies that aim to oppress the people for the sake of the ruler. In this case, by adhering to the basic philosophy of democracy guided by the wisdom of deliberation and representation, the holding of general elections as a means of implementing people’s sovereignty in Indonesia must not deviate from the ideals and objectives of the formation of a Government of the State of Indonesia to protect all Indonesian people and all of Indonesia’s territory, advance public welfare, improve the life of the nation, and participate in implementing world order based on independence, eternal peace and social justice as mandated by the constitution.